2020
DOI: 10.1111/pace.13940
|View full text |Cite
|
Sign up to set email alerts
|

Axillary vein access for permanent pacemaker and implantable cardioverter defibrillator implantation: Fluoroscopy compared to ultrasound

Abstract: Background Axillary vein access (AVA) using fluoroscopic landmarks is an effective and safe approach for cardiac implantable electronic devices (CIEDs) implantation. However, it may result in a higher radiation exposure. Ultrasound‐guided axillary access (USAA) is an effective alternative technique to conventional subclavian access for CIEDs implantation. Studies comparing USAA and AVA using fluoroscopic landmarks are lacking. The purpose of this study was to compare the safety, efficacy, and radiation exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 19 publications
4
31
0
Order By: Relevance
“…Lin et al 22 had previously reported a trend towards reduced fluoroscopy with UGAVA versus traditional techniques while Squara et al 10 reported no difference in fluoroscopy time with UGAVA versus cephalic vein access 10 . Additionally, Migliore et al 23 also reported reduced reduction in fluoroscopy time in patients undergoing UGAVA compared to fluoroscopic landmarks. While UGAVA can be done without fluoroscopy, our operators would routinely confirm wire presence within the inferior vena cava or the right ventricle as confirmation of venous rather than arterial access.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al 22 had previously reported a trend towards reduced fluoroscopy with UGAVA versus traditional techniques while Squara et al 10 reported no difference in fluoroscopy time with UGAVA versus cephalic vein access 10 . Additionally, Migliore et al 23 also reported reduced reduction in fluoroscopy time in patients undergoing UGAVA compared to fluoroscopic landmarks. While UGAVA can be done without fluoroscopy, our operators would routinely confirm wire presence within the inferior vena cava or the right ventricle as confirmation of venous rather than arterial access.…”
Section: Discussionmentioning
confidence: 99%
“…This study otherwise adds to prior observational data suggesting that when compared to fluoroscopy-based axillary/subclavian vein access techniques, US guidance is safe and successful in >90% of patients with a trend towards reduced fluoroscopy use and no impact on total implant time [8][9][10].…”
mentioning
confidence: 61%
“…A significant limitation to note in the current study and several others [8][9][10][11][12] is the reliance on data gathered from one or two operators with experience in ultrasound-guided axillary vein access. It does not account for the learning curve, which would be encountered by new adopters.…”
mentioning
confidence: 98%
“…This study otherwise adds to prior observational data suggesting that when compared to fluoroscopy‐based axillary or subclavian vein access techniques, US guidance is safe and successful in greater than 90% of patients with a trend towards reduced fluoroscopy use and no impact on total implant time 8–10 …”
mentioning
confidence: 66%
“…A significant limitation to note in the current study and several others 8–12 is the reliance on data gathered from one or two operators with experience in ultrasound‐guided axillary vein access. This does not account for the learning curve, which would be encountered by new adopters.…”
mentioning
confidence: 97%